Multikultural dalam Perspektif Ajaran Islam - Khoirul Anam Siddeh; Dhewanty Indriani; Wahyu Candra Pratama (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The concept of multicultural education from an Islamic perspective is an effort to build a harmonious community life amidst ethnic, cultural, racial, and religious diversity. This paper aims to explain the definition, principles, and values of multicultural education in Islam. The method used is a literature study by examining various scientific sources, the Quran, and the opinions of experts regarding multicultural education. The results of the discussion indicate that Islam views diversity as a divine law that must be accepted and respected. Multicultural education in Islam is based on the values of monotheism, equality, tolerance (tasamuh), justice ('adl), brotherhood (ukhuwah), and peace. These principles are realized through mutual respect, dialogue, cooperation, and peaceful conflict resolution. Furthermore, values such as mercy, tolerance, tolerance, and kinship are fundamental in shaping the humanistic and inclusive character of students.